2021
DOI: 10.1186/s12957-021-02341-z
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration of thyroid papillary cancer tissue with myeloid leukemic cells: a case report

Abstract: Background Extramedullary leukemia, also known as myeloid sarcoma, is a rare form of acute myeloid leukemia and often accompanies bone marrow involvement. Myeloid infiltration of the thyroid gland is extremely rare. Here, a unique case in which thyroid cancer tissue was infiltrated with myeloid cells is presented. Case presentation We present a case of thyroid papillary cancer infiltrated by blastic cells and bilateral breast and axillary myeloid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Due to the rarity of the case and lack of randomized clinical trials, there is no standardized treatment strategy. The modalities of treatment available include systemic chemotherapy, local radiotherapy, allogeneic bone marrow transplantation, targeted therapy, and immunotherapy [ 2 , 9 ]. Local therapy with surgery or radiotheraphy alone is considered ineffective due to the high risk of recurrence and progression to AML.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Due to the rarity of the case and lack of randomized clinical trials, there is no standardized treatment strategy. The modalities of treatment available include systemic chemotherapy, local radiotherapy, allogeneic bone marrow transplantation, targeted therapy, and immunotherapy [ 2 , 9 ]. Local therapy with surgery or radiotheraphy alone is considered ineffective due to the high risk of recurrence and progression to AML.…”
Section: Discussionmentioning
confidence: 99%
“…However, local therapy combined with systemic chemotherapy is a preferred option. Various AML chemotherapy-like regimens have been used in MS, including idarubicin and cytarabine; cyclophosphamide, cytarabine, topotecan, and granulocyte colony-stimulating factor (G-CSF) (CATG); fludarabine, cytarabine, idarubicin, and G-CSF (FLAG); and daunorubicin and cytarabine [ 9 ]. Tsimberidou et al reported a 69% complete remission rate of isolated MS with cytarabine, idarubicin, and fludarabine [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations